Pengaruh Taut Silang Natrium Tripolifosfat Dengan Kitosan Terhadap Sifat Fisis Chitosan Edible Film Sebagai Drug Delivery System - Mutiara Putri Utami Susanto (Sainteks: Jurnal Sain dan Teknik, 2019)
Chitosan extracted from shrimp waste has been used as material for making edible film. Chitosan edible film can be applied as a medium for drug delivery system. For example, the sample of antibiotic drug used was salicylic acid. To control the characteristics of edible film and drug release, crosslinking need to be added in the making of edible film of chitosan with STPP as crosslinker. This study aims the effect of crosslinker STPP to the physical properties from chitosan edible film (CEF). The experiment methods consisted of three main processes : (1) preparing of CEF with variations of STPP (0; 0.05; 0.1; 0.2% m STPP / V solution), (2). Analizing physical properties of CEF are tensile strength, percent elongation of break, and swelling. Physical properties of CEF were measured for tensile strength, percent elongation of break, and percent of swelling. The results that the addition of STPP affect the physical characteristics of the CEF. As the addition of STTP was increased, the tensile strength increased , percentage of elongation decreased, and swelling decreased.